The luminescent quantum efficiency of $latex Cr ^{3+}$ ions in co-doped crystals of $latex LiNbO_ {3} : ZnO$ determined by simultaneous multiple-wavelength photoacoustic and luminescence experiments - Torchia, Gustavo Adrián (2001)
In this paper, the luminescent quantum efficiency of $latex Cr ^{3+}$ ions in co-doped crystals of $latex LiNbO_{3} : ZnO : Cr ^{3+}$ is determined by using a method based on simultaneous multiple-wavelength measurement of photoacoustic and luminescence signal after pulsed laser excitation. The quantum efficiency found in this lattice was (10±4)%. This result was compared with the value found from the study of the lifetime in terms of the temperature of the luminescent levels involved. In this last case, two non-equivalent crystal sites were found for $latex Cr^{3+}$ ions, and two fluorescence quantum yields were determined. After the estimation of the concentration of each site by electron paramagnetic resonance experiments, the averaged fluorescence quantum yield value was (9±2)% in agreement with the previous result.